2020
DOI: 10.1371/journal.pone.0238730
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes of Lebanese women towards Baby Friendly Hospital Initiative practices

Abstract: Background The World Health Organization and United Nations Children's Fund launched the Baby Friendly Hospital Initiative (BFHI) to encourage best infant breastfeeding practices immediately after birth. In Lebanon, few hospitals are currently accredited as Baby Friendly. Aim To assess the knowledge of Lebanese women of BFHI steps, and to explore their attitudes towards Baby Friendly Hospitals, Skin-to-Skin Contact and Kangaroo Care practices. Methods A cross-sectional survey of a random sample of healthy preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…perception of colostrum being stale milk that stayed in the breast for the nine months of pregnancy [ 132 ]. In Lebanon, the majority of pregnant women who were surveyed for a study were unfamiliar with the terms baby friendly hospital, skin-to-skin contact or kangaroo care [ 143 ].…”
Section: Resultsmentioning
confidence: 99%
“…perception of colostrum being stale milk that stayed in the breast for the nine months of pregnancy [ 132 ]. In Lebanon, the majority of pregnant women who were surveyed for a study were unfamiliar with the terms baby friendly hospital, skin-to-skin contact or kangaroo care [ 143 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the meantime, the number of under-5 children who are overweight has risen from 33.3 million in 2000 to 38.9 million in 2020 [ 11 ]. Before the COVID-19 pandemic, chronic childhood malnutrition remained a major challenge in the EMR, including Lebanon, which has been known to have low rate of breastfeeding [ 12 ] of which only about 14.8% of infants under the age of six months experienced exclusive breastfeeding in 2015 [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, no study has reported the prevalence of introducing complementary feeding before 6 months in Lebanon. Lebanon, a middle-income country, has a low rate of breastfeeding ( 17 ). Misconceptions about breastfeeding among mothers and communities, a lack of professional lactation support, a failure to implement national policies that promote and protect breastfeeding practices, a lack of social support, particularly at the family level, and other socio-demographic factors are all barriers to breastfeeding ( 18 ).…”
Section: Introductionmentioning
confidence: 99%